2022
DOI: 10.1371/journal.ppat.1010385
|View full text |Cite
|
Sign up to set email alerts
|

The glycerol-3-phosphate dehydrogenases GpsA and GlpD constitute the oxidoreductive metabolic linchpin for Lyme disease spirochete host infectivity and persistence in the tick

Abstract: We have identified GpsA, a predicted glycerol-3-phosphate dehydrogenase, as a virulence factor in the Lyme disease spirochete Borrelia (Borreliella) burgdorferi: GpsA is essential for murine infection and crucial for persistence of the spirochete in the tick. B. burgdorferi has a limited biosynthetic and metabolic capacity; the linchpin connecting central carbohydrate and lipid metabolism is at the interconversion of glycerol-3-phosphate and dihydroxyacetone phosphate, catalyzed by GpsA and another glycerol-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…In our analysis, glycerol 3‐phosphate (Gro3P) was found to be the metabolite with the greatest fold change difference between the Δ bb0318 mutant and wild‐type B. burgdorferi (Figure 1b and Table S2). In B. burgdorferi , Gro3P is generated by the reduction of the glycolysis intermediate dihydroxyacetone phosphate (DHAP) by GpsA/BB0368 (Drecktrah et al, 2022) and/or phosphorylation of imported glycerol by GlpK/BB0241, a putative glycerol kinase (Schwan et al, 2003). In addition, Gro3P is believed to be converted to DHAP by a putative Gro3P dehydrogenase, GlpD/BB0243 (Fraser et al, 1997; Gherardini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our analysis, glycerol 3‐phosphate (Gro3P) was found to be the metabolite with the greatest fold change difference between the Δ bb0318 mutant and wild‐type B. burgdorferi (Figure 1b and Table S2). In B. burgdorferi , Gro3P is generated by the reduction of the glycolysis intermediate dihydroxyacetone phosphate (DHAP) by GpsA/BB0368 (Drecktrah et al, 2022) and/or phosphorylation of imported glycerol by GlpK/BB0241, a putative glycerol kinase (Schwan et al, 2003). In addition, Gro3P is believed to be converted to DHAP by a putative Gro3P dehydrogenase, GlpD/BB0243 (Fraser et al, 1997; Gherardini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated that the complementary activities of GlpD and GpsA control the intracellular pool of Gro3P (Drecktrah et al, 2022). Therefore, beyond decreased activity of GlpD due to FAD deficiency, we explored the possibility that the accumulation of Gro3P in the absence of bb0318 may have resulted from dysregulation of glpD or gpsA expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One such essential gene, gpsA , is a predicted glycerol-3-phosphate dehydrogenase, and it is involved in phospholipid synthesis. Previous research has identified gpsA as a virulence factor in Lyme disease, as well as enhancing nasopharyngeal colonization of Streptococcus pneumoniae (Drecktrah et al, 2022; Green et al, 2021). Another conserved essential gene, suhB , is an inositol monophosphatase.…”
Section: Discussionmentioning
confidence: 99%